Endoscopic dacryocystorhinostomy with and without silicone stenting: A comparative study - K. Shashidhar; Umesh Nagalotimath; Deepika Dixit (Al Ameen Medical College, 2014)
Background and objectives: The objective of the present study is to compare the results of performing endonasal dacryocystorhinostomy for primary nasolacrimal duct obstruction with and without silicone stenting. Methods: This is a prospective randomized study including 57 patients who underwent 62 endonasal DCR procedures. 32 eyes underwent DCR with bicanalicular silicone stenting which was kept for 6 weeks. 30 eyes underwent DCR without stenting. Follow up was done for 6 months. Outcome of the surgery was noted as success in terms of complete relief from epiphora, patency of the ostium assessed by nasal endoscopy and lacrimal sac syringing. Results: The overall success rate for endoscopic endonasal DCR was 90.3%. Success rates were 93.7% with stenting and 86.7% without stenting. There was no statistical difference in the outcome of the two groups (p=0.4180). Complications noted were granulations, synechiae, periorbital edema and punctal trauma, with no difference in the frequency of occurrence in the two groups. Conclusion: There is no significant increase in the success rates of DCR on using silicone stenting. A selective stenting approach may be advocated, using stenting for specific indications. With proper technique and good follow up, stenting is not associated with any significant complications.